The role of working women performance in improving reality of provided health services in health centers in Latakia Governorate from the point of view of beneficiaries - طه نسرين; أسامة محمد (Latakia University Journal - Arts and Humanities Sciences Series, 2023)
The issue of health has become the most important in the field of development, as one of the most important factors contributing to the achievement of sustainable development and one of its indicators. Based on the fact development requires all human energies, attention began to be paid to women in order to provide with knowledge, skills and expertise that enable them to contribute to development, and any disruption of their role is a disruption to half of the strength of society, the study aimed to identify the contribution of women in government centers in Latakia governorate, and performance of working women in improving reality of services provided in health centers in Latakia Governorate. In addition to submitting scientific proposals that contribute to activating the role of Syrian women in health development. The research adopted the descriptive analytical approach, 385 questionnaires were distributed and 377 questionnaires were retrieved, 7 questionnaires were rejected for incomplete answers, and the final number subject to analysis reached 370, appropriate statistical methods used to reach the recommendations, the most important of which are: increasing attention to the process of training, skills development and capacity building, relying on modern measures in evaluating the performance of workers, and motivating creative workers financially and.emotionally.